The role of a neuropsychiatry clinic in a tertiary referral teaching hospital: a 2-year study. (30th July 2014) - Jabbar, F.; Doherty, A.; Duffy, R.; Aziz, M.; Casey, P.; Sheehan, J.; Lynch, T.; Kelly, B. D.
Abstract : Objectives: Mental disorder is common among individuals with neurological illness. We aimed to characterise the patient population referred for psychiatry assessment at a tertiary neurology service in terms of neurological and psychiatric diagnoses and interventions provided. Methods: We studied all individuals referred for psychiatry assessment at a tertiary neurology service over a 2-year period ( n = 82). Results: The most common neurological diagnoses among those referred were epilepsy (16%), Parkinson's disease (15%) and multiple sclerosis (8%). The most common reasons for psychiatric assessment were low mood or anxiety (48%) and medically unexplained symptoms or apparent functional or psychogenic disease (21%). The most common diagnoses among those with mental disorder were mood disorders (62%), and neurotic, stress-related and somatoform disorders, including dissociative (conversion) disorders (28%). Psychiatric diagnosis was not related to gender, neurological diagnosis or psychiatric history. Conclusion: Individuals with neurological illness demonstrate significant symptoms of a range of mental disorders. There is a need for further research into the characteristics and distribution of mental disorder in individuals with neurological illness, and for the enhancement of integrated psychiatric and neurological services to address the comorbidities demonstrated in this population.